Effect of Endometrium Thickness on Clinical Outcomes in Luteal Phase Short-Acting GnRH-a Long Protocol and GnRH-Ant Protocol - Zhang, Jie; Sun, Yi-Fei; Xu, Yue-Ming; Shi, Bao-jun; Han, Yan; Luo, Zhuo-Ye; Zhao, Zhi-Ming; Hao, Gui-Min; Gao, Bu-Lang (Frontiers in Endocrinology, 2021)
Objective: To investigate the influence factors of luteal phase short-acting gonadotropin-releasing hormone agonist (GnRH-a) long protocol and GnRH-antagonist (GnRH-ant) protocol on pregnancy outcome and quantify the influence. 5.About the statistical analysis, it is not correct for the Number of gravidities. Methods: Infertile patients (n=4631) with fresh in-vitro fertilization /intracytoplasmic sperm injection (IVF/ICSI) and embryo transfer were divided into GnRH-a long protocol (n=3104) and GnRH-ant (n=1527) protocol groups and subgroups G1 (EMT≤ 7mm), G2 (7mm